Trends of Football Research Publications: A Bibliometric Analysis - Frans Bisulu; Sri Risky Handayani; Risnawati (Journal of Physical Education Health and Sport, 2026)
Football is one of the most widely studied sports in physical education research, yet comprehensive mapping of its publication trends remains limited, particularly in the context of developing regions. This research aims to analyze the development of football research thru a bibliometric analysis approach on published research subjects, in order to identify trends in the number of publications, citation trends, journals with the highest number of publications, researcher trends, as well as patterns of research topic relationships thru network visualization, overlay visualization, and density visualization. This research is based on a literature review conducted thru the Scopus database using the Dimensions application, with the assistance of VOSviewer software version 1.6.20. The PRISMA flow diagram (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) is used as a reporting guideline that includes the stages of identification, screening, and study eligibility. The analyzed data includes football research publications released within the period from 2020 to 2025. The results show a consistent increase in football research publications from 2020 to 2024, with 454 articles analyzed. Network visualization identified three research clusters: quantitative-experimental approaches (dominated by SPSS, post-test, and experimental group), qualitative-process approaches (process, experience, value), and outcome-oriented studies. Overlay visualization confirms that experimental and statistical analysis topics are the most recent and active research trends, while a novelty gap exists in integrating statistical methods with process-oriented learning studies.. Thus, current research trends are more focused on experimental approaches and statistical analysis in the context of education.